Respuesta :
In looking for f(g(x)), one has to substitute the expression of g(x) in place of the variable "x" in f(x). This is shown below:
Given:
f(x) = 9x - 2
g(x) = -x + 3
f(g(x)) = 9(-x + 3) - 2
f(g(x)) = -9x + 27 - 2
f(g(x)) = -9x + 25
Given:
f(x) = 9x - 2
g(x) = -x + 3
f(g(x)) = 9(-x + 3) - 2
f(g(x)) = -9x + 27 - 2
f(g(x)) = -9x + 25
f(x)= 9x-2
g(x)= -x +3
g(x)= -x+3
f(g(x))= 9(-x+3) -2
f(g(x))= -9x+27-2
Answer:
-9x+ 25
g(x)= -x +3
g(x)= -x+3
f(g(x))= 9(-x+3) -2
f(g(x))= -9x+27-2
Answer:
-9x+ 25